Resonant energy transfer from nanocrystal Si to β-FeSi2 in hybrid Si/β-FeSi2 film - 何久洋 张祺桢 吴兴龙 朱剑豪 (中国物理B：英文版, 2013)
The photoluminescence （PL） characteristics of hybrid β-FeSi2/Si and pure β-FeSi2 films fabricated by pulsed laser deposition at 20 K are investigated. The intensity of the 1.54-μm PL from the former is enhanced, but the enhancement vanishes when the excitation wavelength is larger than the widened band gap of Si nanocrystal. Time-resolved PL decay measurements reveal that the lifetime of the photo-excited carriers in the hybrid β-FeSi2/Si film is longer than that in the pure β-FeSi2 film, providing evidence that the PL enhancement results from the resonant charge transfer from nanocrystalline Si to β-FeSi2.